Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas Berbasis Web : Studi Kasus pada Praktik Dr.Aminah Barabai - Ahmad Juliadi; Nadia Puteri Utami; Muhammad Bahit (Indonesian Journal of Applied Accounting and Finance, 2021)
Accounting information system (AIS) is a system that is useful for collecting, storing and processing financial and accounting data used by decision makers. Accounting information is a generally computer-based system and method for tracking accounting activities in relation to information technology resources. This study aims to create an accounting information system for cash receipts and disbursements. The method used is R&D (research and development) for making an accounting information system for cash receipts and cash disbursements, a case study in the practice of dr.AMINAH Barabai. The results of this study can be used as a web-based cash receipt and disbursement application program and can help dr.Aminah's practice to record patient data, record transactions and find out information related to cash receipts and disbursements.